2019
DOI: 10.1002/adsc.201801676
|View full text |Cite
|
Sign up to set email alerts
|

The Employment of Sodium Hydride as a Michael Donor in Palladium‐catalyzed Reductions of α, β‐Unsaturated Carbonyl Compounds

Abstract: Sodium hydride was employed as a Michael donor under the catalysis of PdCl 2 for 1,4conjugate reductions of a, b-unsaturated carbonyl compounds, which features operational simplicity, mild conditions and high atom-economy. The merits of NaH as a reductant were demonstrated by the one-pot or cascade reactions for the syntheses of complex molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…12 In the same year, Zhang and co-workers developed a palladium catalysed hydrogenation for the a,b-unsaturated compounds using sodium hydride as a Michael donor (Scheme 1b). 13 In 2013, Zhang and co-workers have disclosed an iridium catalysed asymmetric hydrogenation of a-alkylidene succinimides derivatives under very high pressure (H2, 20 bar Scheme 1c). 14 However, all of these methods relied on the use of expensive metal catalysts, strong bases or hydrogen gas at very high pressure.…”
Section: Scheme 1: Methods For the Hydrogenation Of Different Electron Deficient Alkenesmentioning
confidence: 99%
“…12 In the same year, Zhang and co-workers developed a palladium catalysed hydrogenation for the a,b-unsaturated compounds using sodium hydride as a Michael donor (Scheme 1b). 13 In 2013, Zhang and co-workers have disclosed an iridium catalysed asymmetric hydrogenation of a-alkylidene succinimides derivatives under very high pressure (H2, 20 bar Scheme 1c). 14 However, all of these methods relied on the use of expensive metal catalysts, strong bases or hydrogen gas at very high pressure.…”
Section: Scheme 1: Methods For the Hydrogenation Of Different Electron Deficient Alkenesmentioning
confidence: 99%
“…α‐COOEt‐Chalcones ( E ‐isomer) were also prepared using piperidine and acetic acid in refluxed benzene using the Dean‐stark apparatus [7,32] . Piperidine and acetic acid were additionally used by other people; [25–26] however, they used solvents other than benzene. The stereochemistry of their prepared chalcones was proven to be E ‐configuration based on the 3 J C‐H coupling constants of C ketone‐H and C ester‐H [32] .…”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%
“…Figure 9 shows the general reaction along with some examples of the prepared indenes. Other α‐amide, α‐COOEt, and α‐keto chalcones were prepared, along with other compounds, in order to study 1,4‐conjugate reduction of 1,3‐dicarbonyls [26] . The reduction was accomplished using sodium hydride that was employed as a Michael donor in the presence of PdCl 2 catalyst as demonstrated in Figure 10.…”
Section: Introductionmentioning
confidence: 99%
“…have shown that 1,3‐diketones can be obtained from carboxylic acids and aromatic ketones in the presence of TFAA and TfOH (Figure 1c) [21] . Recently, in 2019, Liu and his co‐workers reported the synthesis of 1,3‐diketones from ortho ‐ester cinnamate using NaH as the Michael donor (Figure 1d) [22] …”
Section: Introductionmentioning
confidence: 99%
“…[21] Recently, in 2019, Liu and his coworkers reported the synthesis of 1,3-diketones from orthoester cinnamate using NaH as the Michael donor (Figure 1d). [22] The Heck reaction is known for its efficient CÀ C bond formation through the coupling between organic halides and olefins, using pallidum acetate as a conventional source for palladium, which presents a convenient method for carboncarbon bond formation at the unsubstituted vinylic position. [23][24][25][26] When allylic alcohols are used as a source of olefins with aryl halides, the Heck reaction is known to form carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%